An Analytical Study on the Indentation of a Layered Composite Beam and its Utilization in Low Velocity Impact Response - Mehdi Hosseini; Ahmad Ahmadvand (Mechanics of Advanced Composite Structures)
In the present paper, for the first time, the contact problem of a rigid cylindrical indenter and a laminated composite beam is solved using an assumed contact stress approach. Results are presented for contact force - contact length relation and contact stresses. Then, the results of the analysis are generalized to determine the low velocity impact response. The close agreement observed between the present results and those which existed in the literature, confirms the validity and the accuracy of the present analysis. Performing a parametric study, the effects of some important parameters on the indentation and the low velocity impact responses of the composite beam are investigated and discussed. The results reveal that the lay-up [90/90 90/90] gives the maximum contact length and the minimum contact pressure, but, conversely, the lay-up [0/0/0/0] produces the minimum contact length and the maximum contact pressure. The results of the present research can be of great importance in the design and application of layered composite beams.